Noradrenaline and Parkinson's Disease - Delaville, Claire; De Deurwaerdère, Philippe; Benazzouz, Abdelhamid (Frontiers in Systems Neuroscience, 2011)
Parkinson’s disease (PD) is characterized by the degeneration of dopamine (DA) neurons in the substantia nigra pars compacta, and motor symptoms including bradykinesia, rigidity and tremor at rest. These symptoms are manifest when around 70% of striatal DA is lost. In addition to motor deficits, PD is also characterized by the manifestation of non-motor symptoms. However, depletion of DA alone in animal models has failed to simultaneously elicit both the motor and non-motor deficits of PD because the disease is a multi-system disorder that features a profound loss of other neurotransmitter systems. There is growing evidence that additional loss of noradrenaline (NA) neurons of the locus coeruleus, the principal source of NA in the brain, could be involved in the clinical expression of motor as well as in non-motor deficits. In the present review, we analyzed the latest data obtained from animal models of parkinsonism and from parkinsonian patients providing evidence for the implication of NA in the pathophysiology of PD. Recent studies have shown that NA depletion alone or combined with DA depletion resulted in motor as well as in non-motor dysfunctions. In addition, by using selective agonists and antagonists of alpha receptors we, and others, have shown that α2 receptors are implicated in the control of motor activity and that α2 receptor antagonists can improve PD motor symptoms as well as L-Dopa-induced dyskinesia. Here we provide arguments that the loss of NA neurons in PD has an impact on all PD symptoms and that the association of NAergic agents to dopaminergic medication can be beneficial in the treatment of the disease.